The bioremediation potential of filamentous fungi in soil contaminated with lead - Mariconi, Josiane Ribela; Moreira, Hugo Peres; Silva, Leonardo Euripedes de Andrade; Melo, Vanessa Souza Reis; Senhuk, Ana Paula Milla dos Santos; Ferreira, Deusmaque Carneiro; Anhê, Ana Carolina Borella Marfil (Ciência e Natura, 2022)
Population increase resulting from industrial activities has worsened soil contamination with toxic metals. Given the complex dynamics of these pollutants and the complexity of soil matrices, one of the biggest challenges faced by the environmental field lies on developing effective technologies to remediate contaminated soils. Thus, bioremediation may be a decontamination alternative based on using microorganisms. The aims of the current study are to isolate and characterize filamentous fungi with bioremediation potential to be used in soils contaminated with lead. A soil sample was incubated in Sabouraud Caf Agar medium in BOD at 28ºC. CFUs were counted after 72h of incubation; the three most prominently grown colonies were isolated in new plates containing the same medium. Fungi were transferred to liquid submerged fermentation medium with 20 ppm of lead after 24 h of incubation; they remained in shaker incubator at 30°C, 120 rpm, for 120h. Next, the MP-AES analysis was performed to evaluate the final lead concentration. Isolated fungi such as Aspergillus, Penicillium and Trichoderma removed, 56.82%, 66.77% and 75.29% lead ions, respectively, in comparison to the control. Results confirmed the bioremediation potential of these fungi and their possible use in areas contaminated with the herein investigated metal.